Association of HIV-induced immunosuppression and clinical malaria in Nigerian adults - Iroezindu, Michael O; Agabar, Emmanuel I; Daniyam, Comfort A; Okeke, Edith N; Agbaji, Oche O; Agaba, Patricia A; Imade, Godwin E; Idoko, John A (African Journal of Infectious Diseases (AJID), 2012)
Background: Despite the growing body of evidence on the interaction between HIV and malaria in sub-Saharan Africa, there is a dearth of data on clinical malaria in HIV-infected patients in Nigeria. We determined the burden of clinical malaria in HIV-infected adult Nigerians and further investigated the association between their immunological status and the rates of clinical malaria.Methods: Ninety seven antiretroviral treatment-naïve HIV-infected adults were enrolled in a cross-sectional study from August to December, 2009. The participants had a complete clinical evaluation, thick and thin blood films for malaria parasites and CD4 cell count quantification. Clinical malaria was defined as having fever (temperature ≥ 37.5oC or history of fever within 48 hours) and a malaria parasite density above the median value obtained for subjects with co-existing fever and parasitaemia. Results: Clinical malaria was diagnosed in 10 out of 97 patients (10.3%). Lower CD4 cell counts were associated with increasing rates of clinical malaria which was 0% at CD4 cell count of ≥ 500, 2.6% at 200-499 and 30% at <200 cells/µL (χ2= 18.3, p=0.0001). This association remained significant after controlling for other factors in a multivariate analysis (AOR=22.98, 95% C.I: 2.62-20.14, p=0.005). An inverse relationship between CD4 cell count and parasite density was demonstrated (regression co-efficient= - 0.001, p=0.0002).Conclusion: More aggressive malaria control measures are highly needed in severely immunosuppressed HIV-infected patients.